PENGEMBANGAN MODUL UNTUK SISWA KELAS XI IPA PADA MATERI TERMOKIMIA - Mardiana, Mardiana; Harun, A Ifriany Ifriany; Mayasari, Eny (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
This study aims to develop a module using Chemistry subjects, especially on the subject of Thermochemistry, which is able to overcome problems or as an appropriate solution to the current conditions that require students to learn independently at home. The research design used in this research is research and development (Research and Development) or known as RD. The steps in developing modules using Canva, Microsoft Word, and Power Point on chemical thermochemistry material are carried out by following the Analysis, Design, Development or Production, Implementation or Delivery and Evaluations (ADDIE) model. The sample was taken using Purposive Sampling technique. In this study, the respondents used were 40 students from 2 schools, namely Madrasah Aliyah Al-Mustaqim High School with 17 students and Taman Mulia High School with 23 students. This research instrument uses data collection in the form of validation sheets.  Based on the results of module development research on Thermochemistry material, it can be concluded that the module development on Thermochemistry material is based on development. The stages in the development of this Thermochemistry module material start from collecting information obtained through interviews with the XI IPA class teacher, then designing the module design using Microsoft Word, power point, and canva applications. After the product is finished, it is continued with the module validation stage and the assessment of the module product developed is carried out by 3 experts, namely media experts, material experts, and linguists (learning design) by meeting the eligibility criteria. The feasibility assessment of the learning media module obtained very feasible results with a percentage of 77.9% in the media aspect, 78.7% in the material aspect and 82.2% in the language/design aspect. Thus it can be concluded that the development of modules on Thermochemistry material is suitable for learning.